Unusual presentation and location pleural malignant mesothelioma. (10th June 2013) - Kumar, Anjan; Carcano, Carolina; Hadeh, Anas; Lilenbaum, Rogerio
Abstract : Pleural malignant mesothelioma is an uncommon tumour of the thorax. We report two cases: a patient with atypically isolated location of the tumour at the right hilum and a young female patient. The histopathological and radiological features are reviewed with reference to relevant literature.